Repercussões maternas e perinatais de gestantes com cardiopatias em hospital terciário no Ceará - Nascimento, Zeus Peron Barbosa do (2010)
Aims. To evaluate maternal and peri-natal outcomes of pregnant women with heart disease, comparing the socio - demographic, obstetric data and peri-natal results by the type of heart disease (congenital versus acquired) and the route of delivery (vaginal versus abdominal). Methodology. This is a cross sectional, retrospective, descriptive and analytical research carried out by the records of 70 patients who delivered at Hospital Geral Cesar Cals in the years 2007 ( 26 cases) and 2008 (44 cases) by completing questionnaires. We used the Yates chi-square test, Pearson and Fisher Exact test for bi-varied analysis of data. We considered the level of significance p < 0.05. Results. The age of patients ranged from 15 to 42 (mean 25.8 + 6.5) years; on twenty five (35.7%) were first pregnancy, 22 (31.4%) second pregnancy and 23 (32.9%) were multi – pregnancy. Sixteen patients (22.9%) had congenital heart disease and 45 had acquired heart disease (64.3%). There were 15 premature births (21.7%). Twenty four (34.3%) of the women had vaginal deliveries and 46 (65.7%) cesarean section. The rate of pre term births was 21.7%. There was 27.1% of infants with low birth weight, 8.6% of fetal growth restriction, 17.1% of Apgar score < 7 in the first and 11.4% in the fifth minute of life. There was one maternal death and 5 peri-natal deaths. There was no statistical difference between congenital and acquired heart disease except for a greater presence of clinical pathologies previous to the pregnancy in the group of congenital heart disease. Patients who had vaginal deliveries presented higher parity and lower education, higher rates of prematurity in infants with low birth weight and lower Apgar scores in the first minute when compared to those who were submitted to cesarean section. The frequency of clinical discompensation during labor and / or delivery was 5.7% without statistical difference between the vaginal or abdominal. Conclusions. There was a high frequency of cesarean section, premature birth, low birth weight, Apgar score < 7 in the first minute of life and need to be admitted in the neonatal UTI. There was no clear differencebetween the types of heart disease. The worst neonatal results found for the vaginal delivery can be attributed to the very pre-term birth, that is, not necessarily the mode of delivery.